2016
DOI: 10.1093/molehr/gaw037
|View full text |Cite
|
Sign up to set email alerts
|

The study of progesterone action in human myometrial explants

Abstract: This work was supported by grants from the Joint Research Committee of the Westminster Medical School Research Trust, Borne (No. 1067412-7; a sub-charity of the Chelsea and Westminster Health Charity) and the Imperial NIHR Biomedical Research Centre. The views expressed are those of the author(s) and not necessarily those of the NHS or the Department of Health. The authors have no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…Georgiou et al [80] compared gene expression in fresh myometrium, which was frozen at the time of Cesarean section, to ex vivo myometrial pieces, passage 4 primary myometrial cells, and hTERT myometrial cells. While whole-genome transcriptome analysis revealed that none of the in vitro models overlapped with the fresh tissue, in a principal component analysis plot [80], the gene expression profile of the tissue pieces most closely resembled that of the fresh tissue [80]. Upon direct comparison; 1444 genes varied between the ex vivo tissue pieces and fresh tissue; 3840 genes varied between passage 4 primary myometrial cells and fresh tissue; and 4603 genes varied between hTERT myometrial cells and fresh tissue [80].…”
Section: Tissue Pieces/explant Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Georgiou et al [80] compared gene expression in fresh myometrium, which was frozen at the time of Cesarean section, to ex vivo myometrial pieces, passage 4 primary myometrial cells, and hTERT myometrial cells. While whole-genome transcriptome analysis revealed that none of the in vitro models overlapped with the fresh tissue, in a principal component analysis plot [80], the gene expression profile of the tissue pieces most closely resembled that of the fresh tissue [80]. Upon direct comparison; 1444 genes varied between the ex vivo tissue pieces and fresh tissue; 3840 genes varied between passage 4 primary myometrial cells and fresh tissue; and 4603 genes varied between hTERT myometrial cells and fresh tissue [80].…”
Section: Tissue Pieces/explant Modelsmentioning
confidence: 99%
“…While whole-genome transcriptome analysis revealed that none of the in vitro models overlapped with the fresh tissue, in a principal component analysis plot [80], the gene expression profile of the tissue pieces most closely resembled that of the fresh tissue [80]. Upon direct comparison; 1444 genes varied between the ex vivo tissue pieces and fresh tissue; 3840 genes varied between passage 4 primary myometrial cells and fresh tissue; and 4603 genes varied between hTERT myometrial cells and fresh tissue [80]. A total of 555 genes varied commonly upon comparing all three in vitro groups (ex vivo tissue pieces, passage 4 primary myometrial cells and hTERT myometrial cells) to fresh tissue [80].…”
Section: Tissue Pieces/explant Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is known that P4 is an indispensable 32 factor for endometrium decidualization and for early stage of clinical pregnancy to 33 prepare an adequate immune environment for fetus and low LPL results abnormal 34 ongoing pregnancy [18,19,[29][30][31][32]. 35 Forward, it is increasingly clear that embryo implantation is dependent in one side 36 on immune local mechanisms and in another side on endocrine mechanisms related to 37 luteal P4 synthesis while their interactive reaction is still kept into question for 38 pregnancy achievement. For this reason, while our previous work [22] was based on the 39 implementation of PBMC immunotherapy for RIF patients and proving its efficiency 40 tripling the clinical outcomes, the present work was more focused on demonstrating the 41 correlation between LPL and immunotherapy success highlighting the interactive 42 reaction between luteal P4 synthesis by CL and immune system.…”
Section: Introductionmentioning
confidence: 99%
“…119 Nevertheless, it was commonly accepted that with insufficient P4 production causing 120 miscarriages could be solved simply by an exogenous P4 administration in order to 121 regulate the inflammatory mediators of pregnancy and even for patients undergoing IVF 122 process in fresh or frozen cycles to improve clinical outcomes prior embryo 123 transfer [29,35,36]. Indeed, P4 presents an anti-inflammatory action enhancing Th2 124 cytokines production to maintain pregnancy [37,38]. 125 However, our doubled clinical outcomes including implantation and clinical 126 pregnancy rates could have more evident explanation especially when LPL showed high 127 increase in PBMC-test compared to control (9ng/ml vs 4ng/ml) with positive Hypothesis of interactive effect of PBMC immunotherapy and luteal progesterone level for implantation and pregnancy success.…”
mentioning
confidence: 99%